The efficacy and safety of high-dose isoniazid-containing therapy for multidrug-resistant tuberculosis: a systematic review and meta-analysis - Zhou, Ming; Liu, Ai-Mei; Yang, Xiao-Bing; Guan, Cui-Ping; Zhang, Yan-An; Wang, Mao-Shui; Chen, Ya-Li (Frontiers in Pharmacology, 2024)
Accumulating evidence are available on the efficacy of high-dose isoniazid (INH) for multidrug-resistant tuberculosis (MDR-TB) treatment. We aimed to perform a systematic review and meta-analysis to compare clinical efficacy and safety outcomes of high-dose INH-containing therapy against other regimes.We searched the following databases PubMed, Embase, Scopus, Web of Science, CINAHL, the Cochrane Library, and ClinicalTrials.gov. We considered and included any studies comparing treatment success, treatment unsuccess, or adverse events in patients with MDR-TB treated with high-dose INH (>300 mg/day or >5 mg/kg/day).Of a total of 3749 citations screened, 19 studies were included, accounting for 5103 subjects, the risk of bias was low in all studies. The pooled treatment success, death, and adverse events of high-dose INH-containing therapy was 76.5% (95% CI: 70.9-81.8%; I 2 : 92.03%), 7.1% (95% CI: 5.3-9.1%; I 2 : 73.75%), and 61.1% (95% CI: 43.0-77.8%; I 2 : 98.23%), respectively. The high-dose INH administration is associated with significantly higher treatment success (RR: 1.13, 95 % CI: 1.04-1.22; P<0.01) and a lower risk of death (RR: 0.45, 95% CI: 0.32-0.63; P<0.01). However, in terms of other outcomes (such as adverse events, and culture conversion rate), no difference was observed between high-dose INH and other treatment options (all P > 0.05). In addition, no publication bias was observed.In MDR-TB patients, high-dose INH administration is associated with a favorable outcome and acceptable adverse-event profile.